Feedback Amplitude Modulation Synthesis. (30th December 2010) - Kleimola Kleimola, Jari Jari; Lazzarini Lazzarini, Victor Victor; Välimäki Välimäki, Vesa Vesa; Timoney Timoney, Joseph Joseph
Abstract : A recently rediscovered sound synthesis method, which is based on feedback amplitude modulation (FBAM), is investigated. The FBAM system is interpreted as a periodically linear time-varying digital filter, and its stability, aliasing, and scaling properties are considered. Several novel variations of the basic system are derived and analyzed. Separation of the input and the modulation signals in FBAM structures is proposed which helps to create modular sound synthesis and digital audio effects applications. The FBAM is shown to be a powerful and versatile sound synthesis principle, which has similarities to the established distortion synthesis methods, but which is also essentially different from them.